PEMBERDAYAAN SANTRI MELALUI PEMBUATAN PRODUK SABUN ALOEVERA DAN STRATEGI BAURAN PEMASARAN - Suharyati Suharyati; Fitri Yeti; Kery Utami (Jurnal Abdimas Bina Bangsa, 2024)
Pondok Pesantren Al Misbah in Ciseeng, Bogor, integrates religious education with practical skills development to enhance economic self-sufficiency. A service team from the Faculty of Economics and Business at UPN Veteran Jakarta identified opportunities for empowering students by developing aloe vera soap products and their marketing strategies. Aloe vera was chosen for its health and beauty benefits. The aim of this service project is to enhance the economic independence of the students and to broadly introduce the product. The solutions offered include training in the production of aloe vera soap and marketing strategies. Data testing results showed adequate validity and reliability. The activity involved 32 students out of a total of 40, comprising 53% males and 47% females. Through tests, the participants' understanding of marketing strategies and the benefits of aloe vera exceeded the expected target, reaching 87% and 86%, respectively. Moreover, based on the three-box method index calculation, the index value falls in the high category. However, further evaluation is necessary to ensure participants achieve maximum understanding